The effect of 8 weeks of physical training on muscle performance and maximal fat oxidation rates in patients treated with simvastatin and coenzyme Q10 supplementation. (28th December 2021) - Kuhlman, Anja Birk; Mikkelsen, Lise Bluhme; Regnersgaard, Signe; Heinrichsen, Sophie; Nielsen, Frederikke Hyldahl; Frandsen, Jacob; Orlando, Patrick; Silvestri, Sonia; Larsen, Steen; Helge, Jørn Wulff; Dela, Flemming
Abstract : Abstract: Statins are prescribed for the treatment of elevated cholesterol, but they may negatively affect metabolism, muscle performance, and the response to training. Coenzyme Q10 (CoQ10) supplementation may alleviate these effects. Combined simvastatin and CoQ10 treatment during physical training has never been tested. We studied the response to 8 weeks training (maximal oxygen uptake ( V ̇ O 2 max V_O_2max ), fat oxidation (MFO), the workload at which MFO occurred, and muscle strength) in statin naive dyslipidaemic patients who received simvastatin (40 mg/day) with (S + Q, n = 9) or without (S + Pl, n = 10) CoQ10 supplementation (2 × 200 mg/day) or placebo (Pl + Pl, n = 7) in a randomized, double‐blind placebo‐controlled study. V ̇ O 2 max V_O_2max and maximal workload increased with training (main effect of time, P < 0.05). MFO increased from 0.29 ± 0.10, 0.26 ± 0.10, and 0.38 ± 0.09 to 0.42 ± 0.09, 0.38 ± 0.10 and 0.48 ± 0.16 g/min in S + Q, S + Pl, and Pl + Pl, respectively (main effect of time, P = 0.0013). The workload at MFO increased from 75 ± 25, 56 ± 23, and 72 ± 17 to 106 ± 25, 84 ± 13 and 102 ± 31 W in S + Q, S + Pl, and Pl + Pl, respectively (main effect of time, P < 0.0001). Maximal voluntary contraction and rate of force development were unchanged. Exercise improved aerobic physical capacity and simvastatin with or without CoQ10 supplementation did not inhibit this adaptation. The similar increases in MFO and in the workload at which MFO occurred in response to training shows that the ability to adapt substrate selection and oxidation rates is preserved with simvastatin treatment, despite the potential negative impact of simvastatin at the mitochondrial level. CoQ10 supplementation does not augment this adaptation. Key points: Simvastatins are prescribed for treatment of elevated cholesterol, but they may negatively affect metabolism, muscle performance and the response to training. Coenzyme Q10 (CoQ10) supplementation may alleviate some of these effects. We found that simvastatin treatment does not negatively affect training‐induced adaptations of substrate oxidation during exercise. Likewise, maximal oxygen uptake increases with physical training also in patients in treatment with simvastatin. CoQ10 supplementation in simvastatin‐treated patients presents no advantage in the adaptations to physical training Simvastatin treatment decreases plasma concentrations of total CoQ10, but this can be alleviated by simultaneous supplementation with CoQ10 Abstract : Abstract figure legend Statin naive dyslipidaemic patients were treated with simvastatin + CoQ10 or simvastatin + placebo or placebo + placebo while carrying out an exercise training programme. CoQ10 concentrations in plasma increased in the group that received CoQ10 supplementation, but not in the others. If statin was given without CoQ10 supplementation, CoQ10 concentrations decreased in nine out of ten patients. Maximal oxygen uptake ( V ̇ O 2 max V_O_2max ) increased with training in all groups, and maximal fat oxidation capacity (MFO) also increased in all groups.